2019
DOI: 10.1063/1.5096800
|View full text |Cite
|
Sign up to set email alerts
|

Predict-first experiments and modeling of perturbative cold pulses in the DIII-D tokamak

Abstract: Cold pulses are introduced in Ohmic DIII-D tokamak plasmas, revealing for the first time in this machine a quick increase of core electron temperature shortly after the edge cold-pulse injection at low collisionality.The experimental results are consistent with predict-first simulations enabled by the Trapped Gyro-Landau-Fluid (TGLF) transport model. Measurements of electron density evolution during the cold-pulse propagation are enabled by a high time resolution density profile reflectometer. The density evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 69 publications
9
20
0
Order By: Relevance
“…A current study on DIII-D [22] confirms the results obtained on C-Mod. It demonstrates that in low density OH plasmas the rapid density flattening produced by the laser ablation and measured by reflectometry is indeed compatible with the electron heat transport reduction which is required by TGLF to obtain the central temperature increase which is experimentally observed.…”
Section: Introductionsupporting
confidence: 89%
“…A current study on DIII-D [22] confirms the results obtained on C-Mod. It demonstrates that in low density OH plasmas the rapid density flattening produced by the laser ablation and measured by reflectometry is indeed compatible with the electron heat transport reduction which is required by TGLF to obtain the central temperature increase which is experimentally observed.…”
Section: Introductionsupporting
confidence: 89%
“…Then, the transport suppression front propagates inwards in a chain reaction manner. Rapid decrease of the n e gradient possibly plays a role through an off-diagonal contribution as well, as demonstrated in [23,24] for the nonlocal transport study. After the prompt reduction in q e /n e ceases at t − t LH = 1.3 ms, the trajectory in the fluxgradient diagram transits to a different branch with χ HP e ∼ χ PB e , i.e., no stiffness.…”
Section: Resultsmentioning
confidence: 65%
“…2019; Rodriguez-Fernandez et al. 2019; Luda et al. 2020), and database studies have suggested that physics-based models of heating and transport perform equally as well as, if not better than, empirical scalings in predicting performance in present devices.…”
Section: Integrated Modelling Of Sparc Plasmasmentioning
confidence: 99%